Invasion of Popillia japonica in Lombardy, Italy: Interactions with soil entomopathogenic nematodes and native grubs. (26th June 2022) - Glazer, Itamar; Santoiemma, Giacomo; Battisti, Andrea; De Luca, Francesca; Fanelli, Elena; Troccoli, Alberto; Tarasco, Eustachio; Sacchi, Stefano; Bianchi, Alessandro; Gilioli, Gianni; Gherardo, Pamela; Mori, Nicola
Abstract: The recent invasion of the Japanese beetle Popillia japonica Newman (Coleoptera: Scarabaeidae) in northern Italy offered the opportunity to explore the entomopathogenic nematodes (EPNs) associated with the soil of hay meadows. A total of 61 sites were considered for nematode sampling, and from 17 of them (27.9%) EPNs were isolated and further characterized with molecular and morphological techniques as well as with laboratory bioassays. Two main species, Heterorhabditis bacteriophora Poinar (Rhabditida: Heterorhabditidae) and Steinernema carpocapsae Weiser (Rhabditida: Steinernematidae) were recorded with the same frequency together with a few other species (Rhabditida: Oscheius sp. and Phasmarhabditis sp.). The newly isolated EPN populations were characterized for their activity (penetration rate) and infectivity to P. japonica grubs. EPNs occurrence was related to the time of beetle invasion at each sampling site and there was evidence of a density‐dependent response of the EPNs community to P. japonica density. The invasion of P. japonica apparently did not significantly affect the occurrence of native grubs, although a tendency to a decline was observed and should be further investigated.